Autografts, Bone Substitutes, and Combined Approaches for Secondary Alveolar Bone Grafting: A Systematic Review and Meta-Analysis - Baghaei, Saman; Feizbakhsh, Masood; Attar, Bijan Movahedian; Khoshdel, Alireza; Abdali, Hossein (Journal of oral and maxillofacial surgery, 2025)
Alveolar clefts require bone grafting to restore function and esthetics. Although autogenous iliac crest grafts remain gold standard, their morbidity motivates exploration of alternative materials. This systematic review and meta-analysis evaluated 3 approaches to alveolar cleft repair: 1) autogenous bone grafts combined with alternative bone substitute materials (group A), 2) alternative bone substitutes alone (group B), and 3) autogenous iliac crest grafts as the reference standard (group C). Outcomes such as bone density, volume, height, bone formation rates, operative time, and recovery were compared to guide clinical decision-making. A comprehensive search was conducted across the Scopus, PubMed, Web of Science, Cochrane Central, and Embase databases for studies published between January 1, 2000, and July 18, 2024. Medical Subject Heading terms and keywords related to alveolar cleft repair and bone grafting techniques were used, with studies limited to the English-language and peer-reviewed randomized controlled trials. Inclusion criteria focused on randomized controlled trials evaluating secondary alveolar bone grafting with a minimum 6-month follow-up, involving radiographic assessments of cleft regions. Studies on patients with syndromes or primary dentition grafting were excluded. As a result, 3,962 articles were first identified, 15 studies entered the final full evaluation, and eventually, 10 studies with 186 patients met the final criteria. Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines (PRISMA flowchart) were followed, with independent reviewers extracting the data. The risk of bias was assessed using Consolidated Standards of Reporting Trials guidelines. Outcomes were pooled using fixed- and random-effects models as appropriate. The primary outcomes included bone volume, density, height, and bone formation rate. The secondary outcomes were the operative time, hospital stay, and blood loss. Group A achieved the highest bone density and volume retention at 6 and 12 months. Group C demonstrated superior bone formation rates and height but posed greater surgical challenges. Group B offered logistical advantages with reduced invasiveness, but underperformed bone density and formation. These findings emphasize the need for tailored approaches that balance efficacy and patient-specific considerations. These findings underscore the need for personalized approaches in alveolar cleft repair, balancing effectiveness, and patient-specific considerations. Enhanced materials and standardized protocols are vital for optimizing outcomes.